Identification of subsurface structure using the pseudo-gravity method of magnetic data at the geothermal area of Sonai Village and its surroundings, Puriala, Konawe Regency - Ratu, Misbayanti Dian; Manan, Abdul; Bahdad, Bahdad; Chahyani, Rani (Universitas Riau, 2025)
It has been conducted a geomagnetic research in the geothermal area of Sonai Village and its surroundings, Puriala, Konawe Regency, which aims to identify the structure of the subsurface using the pseudo-gravity method. After performing diurnal and IGRF corrections on the measurement data, the residual magnetic field anomaly is obtained around -150 to 90 nT. Furthermore, transformation process using the pseudo-gravity method is carried out, and the anomaly contour density is obtained around -0.07 to 0.06 mGal. The results of 2D modeling of 2 slices on the residual magnetic anomaly map that have undergone pseudo-gravity transformation show that the subsurface layers of the research area are composed of 3 formations. Layers with density values of 1.5 and 2.5 g/cm3 are thought to be Alluvium Deposits in the form of sand and clay, layers with density values of 2.6 and 2.78 g/cm3 are sandstone and conglomerate in the Alangga Formation, and a layer with a density value of 2.84 g/cm3 is peridotite in the Ultramafic Complex (bedrock layer). In addition, several minor faults were also found, and among them 2 minor faults adjacent to geothermal manifestation are located at coordinates of approximately 4o1’16.149” South Latitude dan 122o7’9.609” East Longitude with a distance of ±15 meters, and at coordinates of approximately 4o1’23.388” South Latitude dan 122o7’24.326” East Longitude which is ±28 meters from the manifestation. These minor faults cut through the peridotite layer and the conglomerate layer, and are thought to be the migration path of hot fluids towards the surface.